Murder at Longbourn : a mystery - Kiely, Tracy (New York A Worldwide Mystery, 2009)
Invited to join her Aunt Winnie for a How to Host a Murder Party on New Year's Eve at Winnie's new Cape Cod B and B, Elizabeth Parker must unearth old secrets and new motives in order to clear her beloved aunt of suspicion when the local wealthy miser ends up the unscripted victim.
Keywords: Bed and breakfast accommodations -- Fiction; Cape Cod (Mass.) -- Fiction; Mystery fiction